India's Inflation Process Before and After Flexible Inflation Targeting - Blagrave, Patrick; Lian, Weicheng (Washington, D.C. : International Monetary Fund, 2020)
We study the inflation process in India, focusing on the periods before and after the adoption of flexible inflation-forecast targeting (FIT) in India. Our analysis uses several approaches including standard Phillips curve estimation for headline and core inflation, an examination of the sensitivity of medium-term inflation expectations to inflation surprises, and the properties of convergence between headline and core inflation. Results indicate an important role for domestic factors in driving the inflation process, and there is evidence that expectations have become more anchored since 2015. This result could be attributable to FIT adoption, or to persistently low food prices which dominate the post-FIT-adoption period. The policy implications of these structural changes in the inflation process are investigated using a semi-structural model calibrated to the Indian economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet